Reverse shoulder arthroplasty for type 1 sequelae of a fracture of the proximal humerus - Raiss, Patric; Bruckner, Thomas; Magosch, Petra (The bone & joint journal, 2018)
AimsThe aim of this study was to analyze the results of reverse shoulder arthroplasty (RSA) in patients with type 1 sequelae of a fracture of the proximal humerus in association with rotator cuff deficiency or severe stiffness of the shoulder.Patients and MethodsA total of 38 patients were included: 28 women and ten men. Their mean age at the time of arthroplasty was 73 years (54 to 91). Before the RSA, 18 patients had been treated with open reduction and internal fixation following a fracture. A total of 22 patients had a rotator cuff tear and 11 had severe stiffness of the shoulder with < 0° of external rotation. The mean follow-up was 4.3 years (1.5 to 10). The Constant score and the range of movement of the shoulder were recorded preoperatively and at final follow-up.Preoperatively, radiographs in two planes were performed, as well as CT or arthro-CT scans; radiographs were also performed at final follow-up.ResultsThe mean Constant score improved from 25 points (5 to 47) preoperatively to 57 points (15 to 81) postoperatively. The mean forward elevation of the shoulder increased from 73° (10° to 130°) preoperatively to 117° (15° to 170°) postoperatively. Previous surgery did not influence the outcome. Patients with rotator cuff tears had lower Constant scores than patients without (p = 0.037). Those with preoperative stiffness of the shoulder had lower postoperative external rotation compared with patients without stiffness (p = 0.046). There was no radiographic evidence of loosening. Three complications occurred, leading to revision surgery in two patients. In all, 17 patients rated their result as very good (45%), another 17 as good (45%), two as satisfactory (5%), and two as unsatisfactory (5%).DiscussionRSA is an effective form of treatment for patients with type 1 sequelae of a fracture of the proximal humerus associated with rotator cuff deficiency or stiffness of the shoulder, with high rates of satisfaction. Rotator cuff tears and stiffness of the shoulder had an adverse effect on the clinical outcome.Cite this article: Bone Joint J 2018;100-B:318-23.
Gesehen am 02.04.2019